Exames de imagem do tórax para o diagnóstico da Covid-19:: uma revisão Cochrane - Ebrahimzadeh, Sanam; Islam, Nayaar; Dawit, Haben; Salameh, Jean-Paul; Kazi, Sakib; Fabiano, Nicholas; Treanor, Lee; Absi, Marissa; Ahmad, Faraz; Rooprai, Paul; Al Khalil, Ahmed; Harper, Kelly; et al. (LAJEC - Latin American Journal of Emergency Care, 2024)
-